Shape plasticity in response to water velocity in the freshwater blenny Salaria fluviatilis. Issue 3 (3rd March 2016) - Laporte, M.; Claude, J.; Berrebi, P.; Perret, P.; Magnan, P.
Abstract : A non‐random association between an environmental factor and a given trait could be explained by directional selection (genetic determinism) and by phenotypic plasticity (environmental determinism). A previous study showed a significant relationship between morphology and water velocity in Salaria fluviatilis that conformed to functional expectations. The objective of this study was to test whether this relationship could be explained by phenotypic plasticity. Salaria fluviatilis from a Corsican stream were placed in four experimental channels with different water velocities (0, 10, 20 and 30 cm s −1 ) to test whether there was a morphological response associated with this environmental factor. After 28 days, fish shape changed in response to water velocity without any significant growth. Fish in higher water velocities exhibited a more slender body shape and longer anal and caudal fins. These results indicate a high degree of morphological plasticity in riverine populations of S. fluviatilis and suggest that the previous relationship between morphology and water velocity observed in the field may largely be due to an environmental determinism.